Symbols Used in Tunku Abdul Rahman's Speech Text: an Analysis According to the Relevance Theory: (Penggunaan Simbol dalam Teks Ucapan Tunku Abdul Rahman: Analisis Teori Relevans) (Jurnal Bahasa, 2014)
This is a descriptive study revealing the phenomenon of the language used by Tunku Abdul Rahman (First Prime Minister of Malaysia) using a corpus. The study was carried out to demonstrate that Tunku wisely used symbolism to convey his message to listeners. Symbols in the form of words and phrases are selected for analysis. The symbols used refer to concrete objects, and are already known to the listener. The use of objects in the message may help listeners to interpret the implicit meaning that is to be conveyed. The data were analysed based on the Relevance Theory of Sperber and Wilson (1986, 1995) which emphasizes the cognitive role, that is, involving context, context effects (cognitive) and the processing effort. The study finds that listeners would have been able to interpret the symbols used in the speeches with the meaning desired by Tunku.Keywords: symbol, object, corpus study, relevance theory